2019
DOI: 10.4314/ahs.v19i3.26
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between superficial and intra-operative specimens in diabetic foot infections: results of a cross-sectional Tunisian study

Abstract: Objective: To determine the correlation between superficial, and intra-operative specimens in diabetic foot infections (DFIs).Methods: We conducted a cross-sectional study in patients with DFIs hospitalized in a Tunisian teaching hospital. Superficial specimens were collected for all patients, and intra-operative specimens were collected in operated patients. The specimens were processed using standard microbiology techniques. Antimicrobial susceptibility testing was carried out according to the protocol estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…However, the complete epidemiology and microbiology of foot infections in this population need to be better defined and characterized. Patients with DFUs in SSA mostly present to health facilities with sepsis and gangrene already established, resulting in significant mortality if rapid action is not taken [1][2][3][160][161][162][163][164][165][166][167][168][169][170][171][172][173]. Diabetic foot infection can present with cellulitis (the least invasive), deep soft tissue infection (involving fascia, muscles and deep tissue) or osteomyelitis which generally underlies chronic foot ulcers, developing through the contiguous spread of soft tissue infection in an ulcer to the underlying bone [1][2][3][160][161][162][163][164][165][166][167][168][169][170][171][172][173].…”
Section: Foot Infectionmentioning
confidence: 99%
“…However, the complete epidemiology and microbiology of foot infections in this population need to be better defined and characterized. Patients with DFUs in SSA mostly present to health facilities with sepsis and gangrene already established, resulting in significant mortality if rapid action is not taken [1][2][3][160][161][162][163][164][165][166][167][168][169][170][171][172][173]. Diabetic foot infection can present with cellulitis (the least invasive), deep soft tissue infection (involving fascia, muscles and deep tissue) or osteomyelitis which generally underlies chronic foot ulcers, developing through the contiguous spread of soft tissue infection in an ulcer to the underlying bone [1][2][3][160][161][162][163][164][165][166][167][168][169][170][171][172][173].…”
Section: Foot Infectionmentioning
confidence: 99%
“…Recent Turkish literature [ 17 ], and articles from the Southern Mediterranean [ 17 , 22 , 23 ], Asia [ 24 ] and (Sub)‐Saharan Africa [ 25 , 26 , 27 , 28 , 29 , 30 ], indicate a high prevalence of P. aeruginosa , for which the reasons remain unknow. Several African studies from specialised diabetes centres and hospitals report a >60% resistance to third generation cephalosporins and an increasing resistance towards carbapenems among both, the Gram‐negative and Gram‐positive bacteria [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], whereas in Asia, the microorganisms classified as MDR seem to shift towards more Gram‐negative bacteria [ 17 ]. Unsurprisingly, MDRs in DFI might contribute to a worse clinical prognosis when compared to their susceptible bacterial counterparts [ 17 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the prevalence of S. aureus detected in DFIs was 21.9%. Three previous retrospective studies from different Tunisian hospitals showed that S. aureus was isolated in 9%, 17% and 31% of DFIs [ 8 , 9 , 15 ]. This variation in percentages might be due to a difference in the geographical areas, the method applied to obtain cultural samples and study periods, especially the case of our study which took place during the COVID-19 pandemic and partly explaining the decrease in the number of consulting patients.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic foot infection (DFI), defined as soft tissue or bone infection below the malleoli, is the most common diabetic complication that often leads to hospitalization and non-traumatic lower extremity amputation [ 4 , 5 , 6 ]. Many studies have shown that DFI is polymicrobial [ 7 , 8 , 9 ]. Particularly, S. aureus is the bacteria implicated the most [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation